Gurus on Leadership : a guide to the world's thought-leaders in leadership - Thomas, Mark A. (London : Thorogood Publishing Ltd, 2006)
Presents a one-stop guide to the world's key writers on leadership, their thought and contribution. This book is a listing of the main leadership gurus from Adair to Sun Tzu, their main concepts and approaches. It is a guide to some of the world's business leaders, who they are, what they've done, and their beliefs.
nmn25/07/13
Loans
Keywords: .Leadership; Leardership tool box